Anodal transcranial direct current stimulation over the left dorsolateral prefrontal cortex modulates attention and pain in fibromyalgia: randomized clinical trial - Silva, Adriana Ferreira (2017)
Cognitive dysfunction in fibromyalgia patients has been reported, especially when increased attentional demands are required. Transcranial direct current stimulation (tDCS) over the dorsolateral prefrontal cortex (DLPFC) has been effective in modulating attention. We tested the effects of a single session of tDCS coupled with a Go/No-go task in modulating three distinct attentional networks: alertness, orienting and executive control. Secondarily, the effect on pain measures was evaluated. Forty females with fibromyalgia were randomized to receive active or sham tDCS. Anodal stimulation (1 mA, 20 min) was applied over the DLPFC. Attention indices were assessed using the Attention Network Test (ANT). Heat pain threshold (HPTh) and tolerance (HPTo) were measured. Active compared to sham tDCS led to increased performance in the orienting (mean difference [MD] = 14.63) and executive (MD = 21.00) attention networks. There was no effect on alertness. Active tDCS increased HPTh as compared to sham (MD = 1.93) and HPTo (MD = 1.52). Regression analysis showed the effect on executive attention is mostly independent of the effect on pain. DLPFC may be an important target for neurostimulation therapies in addition to the primary motor cortex for patients who do not respond adequately to neurostimulation therapies.